The Concept of Literary Baltistics: Several Versions - Butkus, Vigmantas (Colloquia, 2017)
This article is comprised of two parts. The first part analyses the traditional concept of Literary Baltistics, based on an ethnolinguistic criterion of commonality which in turn presupposes this academic discipline’s comparativist dimension and situates it within Baltic philology as a whole. This concept encompasses: 1) traditional comparativist studies of the literatures of the two Baltic states (Lithuania and Latvia), both genetic and typological research (the work of Kostas Korsakas, Alfons Vilsons, Kęstutis Nastopka, Silvestras Gaižiūnas, Eva Eglāja-Kristsone, and others); and 2) and poetic Baltistics, which draws mainly on linguopoetic and mythopoetic methodological approaches and is primarily focused on the analysis of manifestations of cross-Baltic phenomena in literature and especially language (the work of Skrimantas Valentas is most notable here). The second part of the article analyses what can be called a functional concept of literary Baltistics. It is especially reinforced in foreign practices of studying Lithuanian and Latvian literatures. This concept encompasses: 1) the tendency of conceptually seeing comparative or traditional studies of Lithuanian or Latvian literature as Baltistics (this tendency is especially noticeable in the work scholars studying these literatures beyond the borders of Lithuania and Latvia); and 2) the tendency to somehow relate (or fuse) literary Baltistics to Baltic literary studies (the work of Radegast Parolek, Friedrich Scholz, and Benedikts Kalnač is mentioned).